2022
DOI: 10.3390/antibiotics11091181
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Propolis from Different Apiaries and Harvesting Years: Towards Propolis Standardization?

Abstract: Global demand for safe, effective and natural products has been increasing in parallel with consumers’ concerns about personal and environmental health. Propolis, a traditional and potentially medicinal product with several health benefits, is a beehive product with a worldwide reputation. However, despite the bioactivities reported, the low productivity and high chemical heterogeneity have been extensively hampering broader industrial uses. To assist in overcoming some of these problems, we prepared and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
5
9
2
Order By: Relevance
“…Moreover, Peixoto et al [ 36 ] reported that blends of five ethanol extracts of propolis from Gerês collected over five different years are equally or even more interesting than the individual extracts, and a step towards standardization since combining less and more active extracts resulted in comparable bioactivities. Similar results were obtained later by the same team while combining ethanol extracts of propolis collected from different apiaries and harvesting years [ 37 ], which further highlights the usefulness of propolis blends to increase the availability and to value this beehive resource. Overall, these studies support the great potential of propolis mixtures and increase the interest and the valorization of this natural product.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, Peixoto et al [ 36 ] reported that blends of five ethanol extracts of propolis from Gerês collected over five different years are equally or even more interesting than the individual extracts, and a step towards standardization since combining less and more active extracts resulted in comparable bioactivities. Similar results were obtained later by the same team while combining ethanol extracts of propolis collected from different apiaries and harvesting years [ 37 ], which further highlights the usefulness of propolis blends to increase the availability and to value this beehive resource. Overall, these studies support the great potential of propolis mixtures and increase the interest and the valorization of this natural product.…”
Section: Introductionsupporting
confidence: 83%
“…This result revealed that mixing propolis retains the best antioxidant effect, which in turn might be related to the higher flavonoid content [ 28 ]. In comparison with the results previously reported for Gerês propolis mixtures extracted with absolute ethanol (mG.EE 100 ) (EC 50 values ranging from 11.8 to 13.7 µg/mL), mG.EE 70 presented a higher antioxidant capacity (EC 50 = 4.73 µg/mL), which can be related to the ethanol concentration used during the extraction process [ 36 , 37 ]. Not only the extraction solvent itself, but also its concentration may interfere with the chemical composition and, consequently, with the biological properties, e.g., the antioxidant potential, as has been reported [ 21 , 28 , 87 , 89 ].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Propolis is a traditional, potentially medicinal product with several health benefits. Marta Peixoto and co-workers investigated the antimicrobial potential of ethanol extracts of propolis collected in Pereiro over a 5-year period (2011–2015) and two distinct apiaries/regions—Pereiro and Gerês—in selected years [ 2 ]. The results showed that a mixture of propolis and ethanol extracts had particularly interesting effects on Bacillus subtilis , Propionibacterium acnes , and Staphylococcus aureus .…”
mentioning
confidence: 99%